Australia's Resources Of Rare Earths - Aert Driessen (The Minerals, Metals and Materials Society, 1992)
Australia has large resources of rare earths -- 4.35 Mt of contained rare-earth oxides (REO) in the demonstrated category and 1.69 Kt in the inferred category. Australia's demonstrated REO resources are contained in about equal proportions in placer deposits, which also host Australia's titanium and zircon resources, and in hard-rock deposits. The largest single deposit of rare earths, at Mount Weld in Western Australia, is contained in regolith overlying a carbonatite pipe. It has a demonstrated resource of 1.73 Mt of contained REO and yttrium oxide. The largest demonstrated resources of REOs in placer deposits are in the Murray Bash, southeastern Australia -- a total of 1.90 Mt of contained RE0 in six deposits. However, the REO-bearing minerals (monazite and xenotime) are of secondary importance and their recovery will be determined by the market for titanium dioxide and zircon. The Murray Basin and other pre-Pleistocene basins offer the greatest potential for discovering more REO resources. Australia produces about 7000 t/year of REO in monazite and xenotime nearly all from Western Australia, as by-product of mineral-sand mining; monazite production is about 12 000 t/year (6600 t REO) and intermittent xenotime production is about 50 t/year (25 t REO). About 8000 t/year of monazite containing about 4400 t REO is not recovered separately, or is lost in tailings, as is an unknown but smaller amount of xenotime.